The phenomenon of marriage of minors in the shadow of the Syrian crisis Field study in the city of Jaramana - Yaghi , Nahla (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The aim of the research is to identify the main reasons that contributed to the emergence of the phenomenon of underage marriage in the shadow of the Syrian crisis, and the effects on the girl in particular, and on the whole society in general, and to make recommendations to alleviate their spread in the Syrian society . A descriptive analytical approach was used in the study of the phenomenon. A questionnaire was designed, divided into two parts: a questionnaire on the characteristics of the sample members. It included 12 words that measure a range of personal and demographic variables such as: age of the minor at marriage, degree of kinship with the husband, educational level of the minor, , The marital status of the minor, the number of children, etc., and the question about the phenomenon of marriage of minors, and included (20) words, showing the factors that led to the marriage and the effects of this marriage . This questionnaire was applied to a sample of married minor women residing in the shelters in the city of Jaramana. The sample was chosen according to the intentional method. The sample was 62 women. The researcher also verified the veracity of the questionnaire by presenting the sample questionnaire to a number of specialized arbitrators , And found that this questionnaire covers most aspects of the subject of the study. Thus, the questionnaire came out in its final form. The study also reached several results, the most important of which are: (The reason for the marriage of minors under the Syrian crisis was due to the harsh conditions suffered by families of the sample , Especially security conditions And physical and social factors, based on the fear of their daughters being exposed to problems affecting their honor, and to alleviate the material burden, especially in families with large number of children, there is a significant relationship between the educational status of the husband and the violence practiced by the wife in the study sample, A significant relationship between the husband’s profession and the violence against the wife in the sample of the study. Early marriage affects the health, psychological and social situation of the minor girl .